2019
DOI: 10.1109/access.2018.2880224
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Metabolic Syndrome Using Genetically Optimised Bayesian ARTMAP

Abstract: Metabolic Syndrome (MetS) constitutes of metabolic abnormalities that lead to noncommunicable diseases, such as type II diabetes, cardiovascular diseases, and cancer. Early and accurate diagnosis of this abnormality is required to prevent its further progression to these diseases. This paper aims to diagnose the risk of MetS using a new non-clinical approach called ''genetically optimized Bayesian adaptive resonance theory mapping'' (GOBAM). We evolve the Bayesian adaptive resonance theory mapping (BAM) by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 87 publications
(95 reference statements)
0
9
0
Order By: Relevance
“…Kakudi et al [62] developed a novel ARTMAP algorithm - the Genetically-Optimized Bayesian ARTMAP (GOBAM) for the early diagnosis and risk prediction of MetS in patients who present with borderline MetSR-F measuremente. ARTMAP is an adaptive artificial system capable of solving the stability-plasticity delima which leads to catastrophic forgetting.…”
Section: What Is the Current State Of Art In Non-clinical Methods Formentioning
confidence: 99%
See 3 more Smart Citations
“…Kakudi et al [62] developed a novel ARTMAP algorithm - the Genetically-Optimized Bayesian ARTMAP (GOBAM) for the early diagnosis and risk prediction of MetS in patients who present with borderline MetSR-F measuremente. ARTMAP is an adaptive artificial system capable of solving the stability-plasticity delima which leads to catastrophic forgetting.…”
Section: What Is the Current State Of Art In Non-clinical Methods Formentioning
confidence: 99%
“…The links are represented as matrix connections that preserver nonlinear associations between attributes[101]. The results of the study showed that there is a strong positive relationship between the diagnosis of MetS, work-related factors and psycho-pathological variables in men and women.Kakudi et al[62] developed a novel ARTMAP algorithm -the Genetically-Optimized Bayesian ARTMAP (GOBAM) for the early diagnosis and risk prediction of MetS in patients who present with borderline MetSR-F measuremente. ARTMAP is an adaptive artificial system capable of solving the stability-plasticity delima which leads to catastrophic forgetting.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies [56], [57], [58], [59], [60], [61], [63], [64] applied ANN in their MetS prediction. Four studies ( [59], [60], [57], [61]) developed various ANN network models trained with the back propagation (BkP) algorithm to predict MetS.…”
Section: Artificial Neural Networkmentioning
confidence: 99%